Intestinal tissue engineering - Somasundaram, M (2016)
Tissue engineering (TE) principles have been successfully clinically applied to treat disease affecting specific organs (e.g. trachea) but developments in some organs has lagged behind. The inability to repair or replace significantly damaged intestinal tissue remains a barrier to improving patient outcomes and the promise of Tissue Engineered Intestine (TEI) that was first made more than 20 years ago, is yet to be realised. This work explored the potential of TEI and literature review formed a basis for developing a clinically transferrable experimental model. It was hypothesised that, porcine large intestine could be retrieved from pigs and decellularized to create a biological scaffold that demonstrated favourable properties for TE, including potential for vascular perfusion and cell engraftment. Novel experiments were performed in intestinal retrieval and decellularization, resulting in scaffolds characterised by a number of methods (e.g. histology, immunohistochemistry). Assessment of the scaffold’s ability to support cell engraftment required development of protocols for isolation and culture of appropriate progenitors, including adipose/ bone marrow derived mesenchymal stromal cells and intestinal organoid units. Finally, in-vitro cultures combining scaffolds and cells were used to assess the ability of scaffolds to promote tissue regeneration. Perfusion decellularization methods proved effective in creating biological scaffolds that retained radiologically demonstrated vascular perfusion networks, permitting a future route for recellularization and/or transplantation. Scaffolds demonstrated retention of essential extracellular matrix components (e.g. glycosaminoglycans, collagen) and an absence of cell nuclei. Mesenchymal stem cells were isolated, cultured and combined in-vitro with scaffolds in an attempted scaled-down seeding model. Control of culture conditions was challenging and results inconclusive with respect to the scaffold’s regenerative potential. The work demonstrates an exciting prospect for biological scaffold development for a clinically transferrable, semi-xenogeneic transplant or drug delivery model but further experiments in scaffold seeding are required to assess the full potential.